Fresh frugie / Nur Syamira Suhaimi, Nur Syafiqah Ramli and Nurain Mohd Rozi - Suhaimi, Nur Syamira; Ramli, Nur Syafiqah; Mohd Rozi, Nurain (2019)
In the changing world nowadays, we always become excited with the new product that is being developed according to our new technology. At this stage is necessary in order to get the detail information about the product, the knowledge of the product details and what features is applied to the improved product, find and analyze suitable target market and also the customer. So, we introduce ourselves as a Manufacturer and supply of Wax Coating for fruits and vegetables. Fresh Frugie is an Eco-friendly, non-ammonia based wax coating, which is completely safe for use on fruits and vegetables. Fresh Frugie wax coating is a product developed for use on fruits and vegetables that are intended to be stored in Cold Storage or are transported over long distances. The classification of our product was identified and we have applied innovation synthesis for our product. Innovation synthesis is defined as combination of existing concepts and factors into new formulation. The detail study of the product have been divided into research and development, product design or features, concept testing, prototype build and also test marketing. For research and development, it is for the idea processing about the product to overcome the problem found from the recent product that has been established at Vigory Specialties Sdn. Bhd. This product target market is wide but we are make a survey that consists of average age for the detail study on target market. From the research and the target market that has been done, a consumer trend canvas (CTC) was completed. The CTC will help to show the summary of the product detail, analysis and target market how the product idea was developed. After that, the product design and the features are the characteristic that has been analyzed. The main objective is to give suggestion on how to improve the product of waxing so that the product will become much more effective and user friendly to all consumers. It is good to make sure the environment are safer by recycle the used cooking oil rather than disposed it to any place that will cause an effect to our lifestyle.